Impact of the COVID-19 pandemic on emergency medical service response to out-of-hospital cardiac arrests in Taiwan: a retrospective observational study. Issue 9 (14th July 2021) - Yu, Jiun-Hao; Liu, Chien-Yu; Chen, Wei-Kung; Yu, Shao-Hua; Huang, Fen-Wei; Yang, Ming-Tzu; Chen, Chih-Yu; Shih, Hong-Mo
Abstract : Background: Emergency medical service (EMS) personnel have high COVID-19 risk during resuscitation. The resuscitation protocol for patients with out-of-hospital cardiac arrest (OHCA) was modified in response to the COVID-19 pandemic. However, how the adjustments in the EMS system affected patients with OHCA remains unclear. Methods: We analysed data from the Taichung OHCA registry system. We compared OHCA outcomes and rescue records for 622 cases during the COVID-19 outbreak period (1 February to 30 April 2020) with those recorded for 570 cases during the same period in 2019. Results: The two periods did not differ significantly with respect to patient age, patient sex, the presence of witnesses or OHCA location. Bystander cardiopulmonary resuscitation and defibrillation with automated external defibrillators were more common in 2020 (52.81% vs 65.76%, p<0.001%,  and 23.51% vs 31.67%, p=0.001, respectively). The EMS response time was longer during the COVID-19 pandemic (445.8±210.2 s in 2020 vs 389.7±201.8 s in 2019, p<0.001). The rate of prehospital return of spontaneous circulation was lower in 2020 (6.49% vs 2.57%, p=0.001); 2019 and 2020 had similar rates of survival discharge (5.96% vs 4.98%). However, significantly fewer cases had favourable neurological function in 2020 (4.21% vs 2.09%, p=0.035). Conclusion: EMS response time for patients with OHCA was prolonged during the COVID-19 pandemic. Early advanced life support by EMS personnel remains crucial for patients with OHCA.